A 3D-Printed Simulator and Teaching Module for Placing S2-Alar-Iliac Screws. Issue 3 (24th June 2019) - Bow, Hansen; Zuckerman, Scott L; Griffith, Brenton; Lewis, Steven; McGruder, Chandler; Pruthi, Sumit; Parker, Scott L
Abstract: BACKGROUND: The concept of the S2-alar-iliac (S2AI) screw was developed approximately one decade ago and has rapidly become an important component of spinal arthrodesis. Two challenges to placing S2AI screws are gaining an intuition for free-hand screw placement trajectory and acquisition of the appropriate radiograph to both guide screw placement and diagnose misplacement. OBJECTIVE: To present the design and manufacture of an S2AI screw placement simulator and teaching module that addresses both challenges. METHODS: This simulator involves using a 3D printer to create a life-sized pelvis. Participants first used this print to practice placing free-hand S2AI screws. Then participants used another print to practice taking radiographs showing the posterior superior iliac spine-anterior superior iliac spine corridor (teardrop) view. RESULTS: The accuracy of screw placement increased from 17 to 80% on the left side and 7 to 100% on the right side. The number of radiographs taken by each participant to obtain the teardrop view decreased after practice with the simulator compared to baseline. CONCLUSION: Practice with the S2AI simulator led to an improved intuition of an appropriate free-hand S2AI screw trajectory and a decrease in the number of radiographs needed for obtaining the correct diagnostic view.